The Influence of the Green Consumption Concept on the Demand for Mass Sports - Lu Zhu; Ki tak Kim; RuBin Qian, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports play an integral part in promoting physical fitness and fostering the advancement of social civilization. Promoting the healthy development of sports involves guiding sports activities to return to green spaces and integrate with nature. This direction and choice are significant. Green sports aims to integrate sports, humanity, and ecology effectively, promoting a coordinated and symbiotic development of the sports industry. To investigate the influence of the green consumption concept on the demand for mass sports. In regions A, B, C, D, and others, we distributed a total of 650 questionnaires between March and May 2020. A total of 627 questionnaires were recovered, resulting in a recovery rate of 96.46%. A total of 595 questionnaires were considered valid, resulting in an effective rate of 94.90%. The study employed questionnaire surveys, mathematical statistics, and logical analysis to analyse the influencing factors, consumption level, and demand structure of mass sports consumption comprehensively and deeply in a province. Based on the results, the study deduced the development trend of mass sports in the province. The standard site density is 4.46 sites per 10,000 individuals, with a building area per person of 0.32m2 and a site area per person of 0.81m2. The sports ground has a total area of 85.78 million metres2, with a building area of 68.55 million metres2. The theme and crucial guarantee for the sustainable development of sports, as well as the focus of mass sports development in a Province in the new era, are correct guidance, reasonable planning, participation of the entire population, and the establishment of a mass sports civilization. In the development of green sports, it is crucial to focus on guiding participants towards the formation of appropriate values. In particular, Athletes and event organisers should prioritise the inherent value of sports and refrain from sacrificing it for the sake of maximising economic gains. It is crucial to prioritise guiding the public towards adopting a proper approach to sports. Exploring the convergence of sports technology and cultural development can help identify a rational path for the intelligent advancement of sustainable sports.